Capacity-constrained renewable power generation development in light of storage cost uncertainty - Desta Fitiwi; Muireann Á. Lynch; Valentin Bertsch (The Economic and Social Research Institute (ESRI), 2019)
The development of sustainable energy sources and their enabling infrastructures are often met by public opposition, resulting in lengthy planning processes. One proposed means of reducing public opposition is constraining the capacity of renewable energy projects onshore, leading to more small-scale, decentralised and possibly community-driven developments. This work computes the effects of same by performing a medium- and long-term generation expansion planning exercise considering two renewable development cases, in which renewable power expansion is spatially constrained to certain degrees, under high and low storage cost regimes. We employ an appropriately designed optimisation model, accounting for network effects, which are largely neglected in previous studies. We apply our study to the future Irish power system under a range of demand and policy scenarios. Irrespective of storage costs, the unconstrained portfolio is marginally cheaper than the constrained one. However, there are substantial differences in the final generation expansion portfolios. The network reinforcement requirements are also greater under the unconstrained approach. Lower storage costs only slightly mitigate the costs of capacity constraints but significantly alter the spatial distribution of generation investments. The differential in costs between the unconstrained and constrained cases increases non-linearly with renewable generation targets.
Keywords: 330; Generation expansion planning; electricity generation mix; renewable integration; constrained energy expansion; community energy; public acceptance